Survey of Interest in Reading Insurance Textbooks and Documents in English for Trisakti STMA Students in the Digital Era - Syakir Syakir; Bagus Suhendar (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2022)
Objectives: to find out the percentage of reading interest of STMA TRISAKTI students, especially in terms of: 1) interest in reading text books and insurance documents in English (print and digital), 2) mastery of the contents of text books and documents - insurance documents in English (printed and digital), 3) mastery of reading methods: Speed Reading and SQ3R, mastery of Skimming and Scanning reading techniques in English (print and digital), 4) understanding of Structure Sentences, Style, Vocabulary, and Insurance Terminology in English (print and digital). Research methods: qualitative, comparative, and simple quantitative, data collection techniques: questionnaires. The results: 1) interest in reading text books by 26% (print) and by 36% (digital), while documents by 74% (print) and by 84% (digital), 2) mastery of the content of reading books text by 10% (print and digital), while documents by 40% (print and digital), 3) Mastery of Speed Reading method by 12%, SQ3R by 6%, Skimming by 16%, Scanning by 52%, 4) Understanding Sentence Structure of textbooks by 60% (print and digital), Sentence Structure of Documents by 42% (print and digital), Language Style of textbooks by 34% (print and digital), Language Style of documents by 42% (print and digital), Vocabulary by 52% (print and digital), Terminology by 44% (print and digital).